Lectura de imágenes como estrategia de aprendizaje en el área de lengua y literatura en los estudiantes del tercer año de educación básica de la escuela de educación básica juan Jacobo Rousseau del cantón Ventanas parroquia Zapotal, recinto San Francisco - Valarezo Ávila, Mary (2017)
The investigation of reading images as a learning strategy in the area of Language and Literature carried out in the children of the 3rd year of General Basic Education of the School of Basic Education Juan Jacobo Rosseau, is done starting from the need to improve the academic performance of students in the area of Language and Literature. The work aims to provide students with a motivating tool that allows them to awaken interest in the area of study, thus developing skills that will allow them to function in the environment that surrounds them, such as text comprehension, analytical skills, interpretation, oral expression and writing. The research consists of the following parts: problematic situation and problem statement where the difficulties presented by the students in the area of Language and Literature are analyzed, a reference framework where we will find a theoretical support that bases the investigation, the third chapter show the results obtained from the research, the interpretation of data that showed that the strategy used by the teacher does not help the student to reach the desired goal in the area of Language and Literature and finally the proposal, whose purpose is to provide a guide didactic for reading images that aims to help improve learning in the area of Language and Literature in children.